Performativity and Sexuality Orientation on Characters in Out in the Dark (2012) Movie: Postcolonial Performativity - Maldini, Aditya Rico; Mustofa, Ali (ppjbsip, 2023)
People who identify as lesbian, gay, bisexual, or transgender (LGBT) are beginning to proliferate worldwide. People become gay for various reasons, such as personal ones, cultural ones, and environmental ones. By employing Butler's postcolonial performativity theory, this study explores the topic of sexualism that differed from the movie Out in the Dark (2012). The study's goals are to demonstrate Nimr and Roy's performative identities, the problems between Israel and Palestine that affect their relationship and background, and what Nimr and Roy experience as homosexual residents of that area. This study uses the postcolonial performativity theory to analyze movies. The research method used is a descriptive qualitative method. The researcher will watch the movie numerous times and examine the two characters in the movie by gathering the words, dialogues, and scene screenshots. The findings show that performativity, environment, culture, surroundings, and nation, are what lead Nimr and Roy to become gay or homosexual. Although Nimr became gay because he was fed up with persecution in Israel yet the LGBT community there did not notice any distinctions, Roy became gay because his surroundings and culture enabled him to be gay. AbstrakLesbian, Gay, Biseksual, dan Transgender (LGBT) telah menyebar ke seluruh dunia. Ada banyak alasan seseorang menjadi homoseksual, termasuk alasan pribadi, budaya, dan lingkungan sosial mereka. Penelitian ini membahas tentang isu seksualitas dalam dalam ranah “queer studies” dalam film Out in the Dark (2012) dengan teori performativitas pascakolonial Butlerian. Penelitian ini bertujuan menunjukkan identitas performativitas pada Nimr dan Roy dan alasan mereka menjadi homoseksual, isu Israel dan Palestina yang memengaruhi hubungan serta latar belakang mereka, dan apa yang mereka alami sebagai homoseksual saat tinggal di kedua negara. Metode penelitian yang digunakan ialah metode kualitatif deskriptif. Penelitian ini menggunakan teori performativitas pascakolonial untuk menganalisis film. Peneliti akan menonton film berkali-kali lalu menganalisis kedua karakter dalam film tersebut dengan mengumpulkan kata-kata, dialog, dan tangkapan layar adegan. Hasil penelitian menunjukkan alasan Nimr dan Roy bisa menjadi gay atau homoseksual tidak lepas dari kondisi seperti lingkungan, budaya, masyarakat sekitar, dan negara. Kemudian cara mereka hidup di dunia heteroseksual sebagai homoseksual. Alasan Roy menjadi homoseksual adalah karena lingkungan dan budayanya yang membuat dia memutuskan untuk menjadi gay; sedangkan Nimr menjadi gay karena dia teralienasi atas diskriminasi di Israel, meskipun kaum LGBT di Tel Aviv tidak mempermasalahkan perbedaan.